Menyeimbangkan Keadilan dan Kepastian Hukum dalam Penetapan Asal Usul Anak: Analisis Maqasid Syariah terhadap Putusan Pengadilan Agama - Yanto Hasyim (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The phenomenon of nikah sirri (unregistered marriage) in Indonesia presents critical challenges in family law, particularly concerning the legal status of children born from such unions. This study examines judicial determinations of child origin by the Religious Courts as a legal mechanism to grant civil legitimacy to children from nikah sirri. Using a normative qualitative approach and analyzing two court decisions (No. 0648/Pdt.P/2018/PA.Lmj and No. 1731/Pdt.P/2022/PA.Jr), the research explores how judges consider the principles of justice, legal certainty, and legal utility through the lens of Gustav Radbruch’s legal philosophy. Findings reveal that judicial reasoning in these cases transcends procedural formalism, reflecting an ethical commitment to the holistic protection of children’s rights. The study applies the Maqasid al-Shari’ah framework to evaluate how such rulings align with the five fundamental objectives of Islamic law (protection of life, lineage, property, intellect, and religion). The legal recognition of a child’s nasab and entitlements is shown to fulfill both statutory requirements and Islamic ethical standards of justice. Thus, this research underscores the need to strengthen the synergy between state law and Islamic moral values, positioning the court not merely as a formal legal apparatus, but as a transformative institution in achieving substantive justice in society.